Aplicación de sangre de drago (croton lechleri) y miel de abeja en laparotomía lateral de bovino (bos taurus) como método de cicatrización en el campus Salache. - Terán Benalcázar, Evelin Gabriela (2020)
Exploratory laparotomy is performed due to problems of the digestive system of cattle, due to the frequency that arise from the extensive and semi-intensive production system used in Ecuador. Therefore, the implementation of natural local healing is required in the reduction of dermal wounds caused not only by surgery, but also contaminated and infected wounds since they are very frequent in domestic animals. The objective of the present investigation was to compare the healing effect of Dragon's Blood, Honey Bee as alternative treatments versus 1% Silver Sulfadiazine, as a conventional treatment, in open wounds due to Bovine exploratory laparotomy at the field level. Two cattle were used that were designated to three treatments, therefore, a total of six cattle older than 3 months of age underwent exploratory laparotomy for the purpose of this study. A 7 cm long incision was made to each animal in the left lateral part, where the corresponding treatment was applied to the designated group, every 24 hours for 15 days and the temperature was taken in ° C. The surface of the wound was assessed by taking measurements with a calibrator at 24h initially, then at 72h, at 120h, at 168h, at 216h, at 264h, at 336h, at 408h, and finally at 504h after the surgery. The results showed significant statistical differences in some measurement parameters between treatments of (p <0.05). The three treatments evaluated by measurement showed similar findings in the process of healing by second intention, however, according to the qualitative analysis of the condition of the wound and costs, it was determined that the best treatment was that of Honey Bee.